The optimization of Transparent‐Desktop service mechanism based on SPICE. (27th May 2016) - Li, Weimin; Wang, Bin; Yu, Jiaqi; Zhu, Chong; Xiao, Sinuo; Sheng, Jinfang
Summary: Desktop virtualization, which is to make the desktop virtual so that users can access any application through the network with any devices at any time and any place, is being widely used now as an emerging trend. However, it is important to further improve this approach while maintaining good user experience. Though the simple protocol for independent computing environments as a virtual desktop solution can achieve a user experience similar to an interaction with a local machine, there are still many deficiencies in it. For instance, it cannot apply to environment of high controllability of user, and the quality of graphic interactive experience is to be improved. In this paper, to meet QoE requirements of user, we build a feasible file transfer and sharing mechanism and propose a graphics subsystem optimization strategy based on simple protocol for independent computing environments (SPICE), namely Transparent Desktop. We also verify that the Transparent Desktop can provide users with ubiquitous desktop services of higher efficiency, stronger user‐controllability and better QoE through the experimental. Copyright © 2016 John Wiley & Sons, Ltd.